Investigative challenges relating to gang-related homicide: senior investigating officers' perspectives. Issue 3 (16th September 2019) - Mozova, Katarina
Abstract : Purpose: The purpose of this paper is to provide the reader with senior investigating officer (SIO) perspectives of their understanding of gang-related homicide and associated investigative challenges. Design/methodology/approach: A phenomenological design was utilised in this study. In sum, 15 SIOs from the Metropolitan Police Service were interviewed using a semi-structured interview and analysed using thematic analysis. Findings: It was found that the original typology of "gang homicide" might be too narrow and focus should be paid to "gang-related homicide", characterised via motive behind the offence. This type of homicide exhibited specific characteristics (e.g. violent nature, large potential scene and pool of suspects) and investigative challenges which made it different from other types of homicide (e.g. complexity, need for more resources, managing unwilling witnesses, managing media interest, specific evidence challenges, need for thorough risk assessments). The need for expertise in the deployment of officers was highlighted and related to the desire for more continuing professional development (CPD). Practical implications: Gang-related homicide is especially challenging, but due to its volume, SIOs in London developed a sort of "muscle memory" – something that other police services do not have, even though the "gang problem" is spreading outside of metropolitan areas. Support for changes (e.g. in the utility of community impact assessment) and non-standard procedures (e.g. consideration of covert operations early on) should be discussed in further training and manual development. More attention needs to be paid to the synthesis of experience, expertise and science, SIOs being especially interested in debriefs and CPD opportunities. Multi-agency training is key for homicide investigators, relating to the complex nature of gang-related homicide and relevant safeguarding issues. Resourcing is a clear issue relating to the increase in gang-related homicide, as well as its investigation. Originality/value: This is the first research into investigative challenges of gang-related homicide in England and Wales, and the findings can be utilised by all police services who may be dealing with gangs in their area. The findings can also support calls for change and development within services.